Health literacy and the Internet: a study on the readability of Australian online health information - Christina Cheng; Matthew Dunn (Elsevier, 2015)
Abstract Objective: Almost 80% of Australian Internet users seek out health information online so the readability of this information is important. This study aimed to evaluate the readability of Australian online health information and determine if it matches the average reading level of Australians. Methods: Two hundred and fifty‐one web pages with information on 12 common health conditions were identified across sectors. Readability was assessed by the Flesch‐Kincaid (F‐K), Simple Measure of Gobbledygook (SMOG) and Flesch Reading Ease (FRE) formulas, with grade 8 adopted as the average Australian reading level. Results: The average reading grade measured by F‐K and SMOG was 10.54 and 12.12 respectively. The mean FRE was 47.54, a 'difficult‐to‐read' score. Only 0.4% of web pages were written at or below grade 8 according to SMOG. Information on dementia was the most difficult to read overall, while obesity was the most difficult among government websites. Conclusions and implications: The findings suggest that the readability of Australian health websites is above the average Australian levels of reading. A quantifiable guideline is needed to ensure online health information accommodates the reading needs of the general public to effectively use the Internet as an enabler of health literacy.